Promotion of nutrition care by Australian fitness businesses: a website analysis. (November 2016) - Barnes, K.; Ball, L.; Desbrow, B.
Abstract: Objectives: To investigate the intention of fitness businesses to promote the provision of nutrition care from personal trainers. Study design: Cross- sectional evaluation of webpage content. Methods: Fitness businesses within two Australian federal electorates were identified using the Fitness Australia list of registered fitness businesses. Inductive content analysis of these fitness business websites and associated social media sites was undertaken to compare website content to the Fitness Australia Position Statement outlining the Roles and Responsibilities of Registered Fitness Professionals. Fitness businesses were classified as 'within scope of practice' if they referred to national nutrition guidelines or dietetic services. 'At risk of being beyond scope' included websites which did not include enough information to definitively state within or beyond scope. Fitness businesses were classified as 'definitely beyond scope of practice' if they advertised nutrition care which clearly extended beyond translation of the national dietary guidelines. Results: Of the businesses reviewed, 15% were within scope despite none referring to a dietitian; 34% were at risk of being beyond scope; and 51% were beyond scope as they advertised nutrition care such as personalized diets without indicating dietetic input. Conclusions: A considerable portion of fitness businesses reviewed advertised their personal trainers as able to provide nutrition care outside the recommended scope of practice. Strategies that help fitness businesses and personal trainers to support clients to have healthy dietary behaviours without extending outside the scope of practice are warranted. Highlights: Fitness businesses advertise that their personal trainers can provide nutrition care. Most nutrition content is at risk of being or definitely outside the scope of practice. This includes diet plans, food/nutrition claims, nutrition counselling, and recipes. Such advertisements misrepresent the roles and limitations of a personal trainer. Education regarding professional roles is warranted for the public and for fitness professionals.